Predictors of Adherence to Antiretroviral Therapy among HIV/AIDS Patients in the Upper West Region of Ghana. (10th December 2013) - Obirikorang, Christian; Selleh, Peter Kuugemah; Abledu, Jubilant Kwame; Fofie, Chris Opoku
Abstract : Background . The effectiveness of ART interventions is only realized in maximal levels of adherence. A near perfect adherence level of >95% is required for the effective suppression of HIV/AIDS virus. The main objective of this study was to identify the sociodemographic and socioeconomic factors that facilitate adherence to antiretroviral therapy among HIV/AIDS patients. Methods . This descriptive cross-sectional study was conducted between March and May 2013 at the Upper West Regional Hospital, Wa. A total of 201 confirmed HIV 1 seropositive subjects (mean age3 6.6 ± 9.9 years) receiving antiretroviral therapy were interviewed using a structured questionnaire. The collected data was analyzed using GraphPad Prism version 5. AP value of <0.05 was considered statistically significant for all statistical analyses. Results . Overall lifetime adherence was found to be 62.2% while medication adherence in the last six months, last three months, last month, and last week were 73.6%, 87.1%, 91.0%, and 86.0%, respectively. The study revealed a positive association between adherence to ART and immunological success, with nonadherence increasing the risk (OR (95% CI): 9.2 (3.2–26.9)) of immunological failure. Univariate logistic regression analysis of the data showed that other ailments and side effects of drug were negatively associated with adherence to ART whereas self-perceived wellness, family support, and regular followup were positively associated with adherence to ART. Conclusion . Regular attendance at followup and family support are vital factors for 100% lifetime medication adherence. Effective counseling sessions on adherence for patients on antiretroviral therapy are paramount for the realization of the purpose of antiretroviral therapy programmes in Ghana.